2014
DOI: 10.1089/scd.2013.0426
|View full text |Cite
|
Sign up to set email alerts
|

Graft of a Tissue-Engineered Neural Scaffold Serves as a Promising Strategy to Restore Myelination after Rat Spinal Cord Transection

Abstract: Remyelination remains a challenging issue in spinal cord injury (SCI). In the present study, we cocultured Schwann cells (SCs) and neural stem cells (NSCs) with overexpression of neurotrophin-3 (NT-3) and its high affinity receptor tyrosine kinase receptor type 3 (TrkC), respectively, in a gelatin sponge (GS) scaffold. This was aimed to generate a tissue-engineered neural scaffold and to investigate whether it could enhance myelination after a complete T10 spinal cord transection in adult rats. Indeed, many NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…The major flaw of complete section is high severity of the injury reflected in slightly elevated mortality rate during the post-trasplantation period comparing to other models with the advantage that any regenerative effect can be attributed exclusively to exogenous treatments. This model together with the hemisection is also very useful to test various “bridging gap” biomaterial or device studies alone or in combination with cell grafts242526272829. Various studies used this model to study the effects of combination of different scaffolds and biomaterials and stem cells on axon regeneration after injury, such as a polymer scaffold with rat bone marrow stem cells3031.…”
Section: Discussionmentioning
confidence: 99%
“…The major flaw of complete section is high severity of the injury reflected in slightly elevated mortality rate during the post-trasplantation period comparing to other models with the advantage that any regenerative effect can be attributed exclusively to exogenous treatments. This model together with the hemisection is also very useful to test various “bridging gap” biomaterial or device studies alone or in combination with cell grafts242526272829. Various studies used this model to study the effects of combination of different scaffolds and biomaterials and stem cells on axon regeneration after injury, such as a polymer scaffold with rat bone marrow stem cells3031.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of movement and sensation occurs in spinal cord injury (SCI) below the level of the injured spinal cord. To date, no efficient treatment has taken place to completely repair SCI . Recently, transplantation of stem and progenitor cells incorporating various types of scaffolds to the injury sites has shown auspicious results for SCI therapy …”
Section: Introductionmentioning
confidence: 99%
“…A variable number of nerve fibers were unmyelinated. Remyelination has been reported in a separate SCI study using NT‐3 overexpressing transgenic Schwann cells 40. A study using LINGO‐1 antagonist showed the presence of many new myelin in lumbar spinal cord of rats41 suggesting therefore that formation of multiple layered myelin sheath in hemisected SCI canine is possible.…”
Section: Discussionmentioning
confidence: 84%